LGBTQ Welcoming Guidelines for Museums: developing a resource for the museum field. (2nd July 2016) - Leitch, Christopher; Youngs, Renae; Gavigan, Annette; Lesperance, Michael; Burns, William James; Cohen-Stratyner, Barbara; Hammond, Paul; Hansen, Jaden
ABSTRACT: Beginning in 2014, the LGBTQ Alliance professional network of the American Alliance of Museums (AAM) met to develop and publish a broad set of LGBTQ Welcoming Guidelines for Museums. The authors sought to help museums be more inclusive of lesbian, gay, bisexual, transgender and queer staff and visitors. The Guidelines conform to the most recent established standards of professional practice in museums and touch on all areas of museum work; they may be viewed as part informational reference, part institutional self-assessment tool. The Guidelines were unveiled at the AAM's 2016 annual meeting, and are now available at no charge online (http://www.aam-us.org/resources/professional-networks/lgbtq ). The LGBTQ Alliance encourages readers to use and review the Guidelines and to make observations, critiques and corrections directly to the current chair, Mike Lesperance (mike@thedesignminds.com ).